A Systematic Review and Meta-analysis of Randomized Controlled Trials on the Effect of Transcranial Magnetic Stimulation on Tinnitus Management - Salma Galal; Naema Ismail; Ghada Niel (University Library System, University of Pittsburgh, 2020)
Introduction: Tinnitus occurs in 10-15% of the world's population. It may lead to hearing loss, depression, and suicidal tendencies, as well as reduced quality of life. The aim of this study was to assess whether Transcranial Magnetic Stimulation (TMS) effectively reduces tinnitus handicapping after six months or more of follow-up. Methods: A systematic review of randomized controlled trials with follow-up of six months was undertaken. The review took place through searching Medline, Science Direct, and Google Scholar databases using the keywords "tinnitus" and "Transcranial Magnetic Stimulation" and limiting the search results to randomized controlled trials (RCTs) conducted on adults (19 years and older) published between 2005-2015. Meta-analysis was performed on the similarly designed studies. Results: Five RCTs with six month follow-up were found conforming to the inclusion criteria. In total, there were 119 patients in the TMS arms and 115 in the placebo arms. However, designs were different between the studies and were therefore not all comparable. Different parameters were used to measure the severity of tinnitus and depression scores. Tinnitus handicapped inventory (THI) was the common measured outcome parameter used in all studies. THI score decreased after the TMS in four studies. Meta-analysis was performed on three similarly designed RCTs with the overall effect being insignificant. Conclusion: TMS reduced the THI score and decreased the severity of tinnitus in 45% of patients and lead to a complete recovery in 32% of cases in one study. However, the meta-analysis demonstrated lack of significant effect of TMS on tinnitus management.